2020
DOI: 10.1097/gme.0000000000001497
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ultra-low dose 0.005% estriol vaginal gel for the treatment of vulvovaginal atrophy in postmenopausal women with early breast cancer treated with nonsteroidal aromatase inhibitors: a phase II, randomized, double-blind, placebo-controlled trial

Abstract: Objective: To assess the efficacy and safety of ultra-low dose 0.005% estriol vaginal gel in women with breast cancer receiving nonsteroidal aromatase inhibitors (NSAIs) and experiencing treatment-related vulvovaginal symptoms and signs. Methods: Women with hormone receptor-positive early breast cancer receiving NSAIs were randomized to either estriol vaginal gel or placebo for 12 weeks. Vaginal maturation, vaginal pH, and total and individual scores of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
0
32
0
3
Order By: Relevance
“…With the gradual increase of age, the activity D gradually decreases, the parathyroid gland gradually increases, and the sex hormones gradually decrease. These changes cause increased osteoclast activity and decreased osteoblast activity ( Delgado et al, 2016 ; Hirschberg et al, 2020 ). In postmenopausal women, in addition to the above factors, there are also the decline in estrone, estradiol, and estriol, which accelerate the decline in osteoblast activity, reduce bone matrix formation, and increase bone resorption ( Fallah et al, 2013 ; Knuplez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the gradual increase of age, the activity D gradually decreases, the parathyroid gland gradually increases, and the sex hormones gradually decrease. These changes cause increased osteoclast activity and decreased osteoblast activity ( Delgado et al, 2016 ; Hirschberg et al, 2020 ). In postmenopausal women, in addition to the above factors, there are also the decline in estrone, estradiol, and estriol, which accelerate the decline in osteoblast activity, reduce bone matrix formation, and increase bone resorption ( Fallah et al, 2013 ; Knuplez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Summary of study characteristics is presented in Tables 1 and 2. Of the 36 studies, 11 described topical interventions; 11 described laser interventions; 8 described psychoeducational interventions; 3 described multimodal approaches; and 3 described pharmacological studies 40-75 . All 22 nonrandomized studies were before-after studies (without a control group), consisting of 17 interventional trials and 5 cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Hirschberg et al [ 192 ], in sixty-one BCS patients receiving AIs (50 received estriol vaginal gel and 11 received placebo), found that ultra-low-dose 0.005% estriol vaginal gel showed efficacy in improving the symptoms and signs of vulvovaginal atrophy and that estriol levels increased initially and normalized by week 12, while estradiol and estrone remained mostly undetectable throughout the study. They concluded that the negligible impact of the product on the levels of estrogens, FSH, and LH supported the safe use of this ultra-low-dose estriol vaginal gel as a treatment option for vulvovaginal atrophy in BCSs receiving AIs [Qa = Good].…”
Section: Current Treatment Options For Genitourinary Syndrome Of Meno...mentioning
confidence: 99%